A 30, 000 yr high-precision eruption history for the andesitic Mt. Taranaki, North Island, New Zealand. Issue 1 (6th February 2017) - Damaschke, Magret; Cronin, Shane J.; Holt, Katherine A.; Bebbington, Mark S.; Hogg, Alan G.
Abstract: Tephra layers from 11 sediment cores were examined from a series of closely spaced lake and peat sites, which form an arc around the andesitic stratovolcano Mt. Taranaki, North Island, New Zealand. A new high-resolution composite tephra-deposition record was built, encompassing at least 228 tephra-producing eruptions over the last 30 cal ka BP and providing a basis for understanding variations in magnitude and frequency of explosive volcanism at a typical andesitic volcano. Intersite correlation and geochemical fingerprinting of almost all tephra layers was achieved using electron microprobe–determined titanomagnetite phenocryst and volcanic glass shard compositions, in conjunction with precise age determination of the tephra layers based on continuous down-core radiocarbon dating. Compositional variation within these data allowed the overall eruption record to be divided into six individual tephra sequences. This geochemical/stratigraphic division provides a broad basis for widening correlation to incomplete tephra sequences, with confident correlations to specific, distal Taranaki-derived tephra layers found as far as 270 km from the volcano. Furthermore, this tephrostratigraphical record is one of the most continuous and detailed for an andesitic stratovolcano. It suggests two general patterns of magmatic evolution, characterized by intricate geochemical variations indicating a complex storage and plumbing system beneath the volcano.